Evaluation of tandem Chlamydia trachomatis MOMP multi-epitopes vaccine in BALB/c mice model. Issue 23 (25th May 2017) - Jiang, Pengfei; Cai, Yiqi; Chen, Jun; Ye, Xiaoxian; Mao, Shanshan; Zhu, Shanli; Xue, Xiangyang; Chen, Shao; Zhang, Lifang
Abstract: Chlamydia trachomatis ( Ct ), an obligate intracellular parasite, is the leading cause of bacterial sexually transmitted diseases worldwide. The best solution to control the spread of Ct is to develop safe and effective vaccines. However, an effective vaccine has not been developed due to some challenges such as selection of appropriate candidate antigens and an effective delivery system. In our previous study, we have developed a Ct vaccine that comprises a multi-epitope peptide of Ct major outer membrane protein (MOMP370–387 ) and Hepatitis B virus core antigen (HBcAg). The vaccine was evaluated in a murine model with chlamydial genital infection. The results indicated that Ct MOMP multi-epitope delivered by HBcAg could be an effective vaccine for the prevention of Ct . In this study, another two epitopes were selected from the MOMP protein and tandemly linked with MOMP370–387 to enhance the immunogenicity and the protective effect of the candidate vaccine. Our results revealed that both the immunogenicity and the protective effect of the tandem Ct MOMP multi-epitopes were much better than that of the single epitope. Therefore, vaccines based on the tandem Ct MOMP multi-epitopes could be more effective immune prophylactics to prevent Ct infection than the single epitope in murine model system.